Analýza fenotypu a kinetiky subpopulací CD34+ bunĕk a lymfocytů dárců periferních hematopoetických kmenových bunĕk pro alogenní transplantace - Klabusay, M; Suková, V; Korístek, Z; Mayer, J; Vorlícek, J (Casopis lekaru ceskych, 2003)
BACKGROUND: Amount of CD34+ cells is a critical parameter for quality assessment and successful engraftment of peripheral blood hematopoietic stem cells (PBSC) during the transplantation of haemopoisis. CD34+ cells are routinely analysed by immunophenotyping in PBSC and in peripheral blood during mobilization. Other leukocyte subpopulations are not usually assessed. METHODS AND RESULTS: The authors present results of immunophenotyping of subpopulations of CD34+ cells and leucocytes in samples from donors of PBSC for allogeneic transplantations, who were stimulated with the growth factor G-CSF at dose 16 micrograms/kg/day. The amount of CD34+ cells was not significantly different between days 4 and 5; however, there was a significant drop at day 6. CD34+90+ and CD34+61+ subpopulations reached their maximum at the day 4; partially differentiated CD34+ cells with co-expression of CD33, CD19, and CD7 reached maximum at the day 6. CD4+ Th-lymphocytes were concentrated in the grafts during leukapheresis, CD4/CD8 ratio in the grafts was increased to average 3.06. CONCLUSIONS: The knowledge of kinetics of CD34+ subpopulations, together with stem cell selection and ex vivo manipulation, may have an impact on the speed of engraftment or GvHD prevention in transplanted patients.
Keywords: podskupiny lymfocytů; Immunophenotyping; imunofenotypizace; Tissue Donors; dárci tkání; rekombinantní proteiny; Lymphocyte Subsets; Antigens, CD34; mobilizace hematopoetických kmenových buněk; faktor stimulující kolonie granulocytů; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; Humans; filgrastim; Granulocyte Colony-Stimulating Factor; Filgrastim; antigeny CD34; Hematopoietic Stem Cell Mobilization; lidé; Recombinant Proteins